Utilization of rabbit skin as edible film for environmentally friendly food packaging using glycerol as plasticizer - Jajang Gumilar; Wendry S. Putranto; Andry Pratama; Rani Maharani (World Rabbit Science, 2025)
The growing rabbit population has directly contributed to increased meat yields and higher production of by-products, including skins. The skin of local Indonesian rabbits is mostly used as fish feed and fertilizer due to the relatively poor quality of their fur. Rabbit skin can potentially be used as a more economical product such as edible film, due to its high protein content of 67.3% and collagen content of 28.8%. Protein and collagen from rabbit skin can be produced into good quality gelatine. Gelatine plays a vital role in developing biodegradable edible film packaging materials. Gelatine films offer a strong barrier against light, air and odour transfer, but they can be too brittle as packaging materials. This problem needs to be overcome by adding plasticizers such as glycerol. The purpose of this study was to investigate the effect of glycerol on the functional groups and physical, mechanical and colour properties of edible films made from rabbit skin gelatine. This experiment employed a completely randomised design with five glycerol treatments (10, 20, 30, 40, and 50%). Each treatment was replicated four times. Data were analysed using ANOVA followed by Tukey’s test. The results show that there is a good affinity between biopolymers from rabbit skin gelatine and glycerol as indicated by the formation of Fourier transform infrared (FTIR) bands. The level of glycerol used has a significant effect (P<0.05) on the mechanical, physical and colour properties. The best edible film from rabbit skin gelatine is produced with 10% glycerol.